The boundedness of a class of semiclassical Fourier integral operators on Sobolev space $H^{s}$ - O. F. Aid; A. Senoussaoui (Математичні Студії)
We introduce the relevant background information that will be used throughout the paper. Following that, we will go over some fundamental concepts from the theory of a particular class of semiclassical Fourier integral operators (symbols and phase functions), which will serve as the starting point for our main goal.